TSIS: A Trust-Based Scheme for Increasing Security in Wireless Sensor Networks - Mahdi Dibaei; Ali Ghaffari (Majlesi Journal of Electrical Engineering)
Security is considered to be one of the most important challenges in wireless sensor networks (WSNs). Due to inherent resource constraints in WSNs, traditional security mechanisms may not be used in these networks. In recent years, trust and reputation management in distributed systems has been proposed as a novel and accurate way for handling security deficiencies. Such deficiencies are deemed to be inherent in WSNs. Detecting malicious nodes is an important role of Trust models in WSNs. In line with reducing the above-mentioned deficiencies, the present paper has proposed a trust-based scheme for increasing security (TSIS) model for WSNs. The proposed trust-based scheme divides the network into some clusters. Inside each cluster, a special node named supervisor node is responsible for calculating the trust values of other nodes. When supervisor nodes calculate trust values of other nodes in a cluster, they do not distribute these values. The receiver node requests the sender node authentication from its own supervisor node. The proposed method was simulated in the NS-2 environment. The simulation results indicate that the proposed method has improved energy efficiency and packet delivery rate. Hence, it has better performance than the earlier works with respect to the above-mentioned parameters.